2014
DOI: 10.1007/s10995-014-1525-9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Caregiver Depression on Children in Non-relative Foster Care Versus Kinship Care Placements

Abstract: Little is known about how the challenges faced by caregivers influence the variation in social, emotional, and behavioral (SEB) outcomes of youth placed in kinship versus non-relative foster care. This study examined SEB symptoms among youth in kinship and non-relative foster care settings, hypothesizing that changes in caregiver depression would modify children's change in behavior over time. Child Behavior Checklist (CBCL) assessments of 199 children placed with kinship and non-relative foster care providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…In a recent study, Heneghan et al (2013) found that youth age 12-17.5 years who were investigated for maltreatment are more than twice as likely to report anxiety when their caregivers report depression than when their caregivers do not endorse depressive symptomatology. These conclusions, coupled with our findings, suggest that to prevent poor mental health outcomes among foster care alumni, child welfare and other public youth serving systems of care must prioritize policies and practices that address the mental health needs of caregivers (Garcia et al 2014). …”
Section: Direct Effects Of Mental Health Outcomessupporting
confidence: 58%
“…In a recent study, Heneghan et al (2013) found that youth age 12-17.5 years who were investigated for maltreatment are more than twice as likely to report anxiety when their caregivers report depression than when their caregivers do not endorse depressive symptomatology. These conclusions, coupled with our findings, suggest that to prevent poor mental health outcomes among foster care alumni, child welfare and other public youth serving systems of care must prioritize policies and practices that address the mental health needs of caregivers (Garcia et al 2014). …”
Section: Direct Effects Of Mental Health Outcomessupporting
confidence: 58%
“…The possible negative effect of caregiving on the psychological health of children raises concerns and requires more attention. Studies have shown that positive or negative changes in a caregiver's child's depression can have corresponding effects in the social, emotional, and behavioral outcomes (Garcia et al., ). And although our results approached significance on the whole, the relative weakness compared to other outcomes deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…It may be a stress burden for caregivers and children to start rehabilitation too early. The benefit of early rehabilitation interventions for preterm infants has been emphasized recently [ 48 ]. The expected outcome of a developmental care intervention is improvement in overall physical, social, cognitive, and emotional development.…”
Section: Discussionmentioning
confidence: 99%